1991
DOI: 10.1001/archsurg.1991.01410250056009
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic Glucocorticoid Levels and Survival of Translocating Bacteria

Abstract: Burn wound sepsis in rats results in sustained corticosterone elevations and the prolonged presence of translocated bacteria in the mesenteric lymph nodes (MLNs). To determine if survival of bacteria in the MLNs may be influenced by pathophysiologic corticosterone levels, MLNs were quantitatively analyzed from rats randomized to the following groups: burn wound sepsis (BI); BI with adrenocortical response attenuated by cyclosporine (cyclosporine/BI); or cyclosporine/BI with corticosterone replacement (cyclospo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Therefore, the administration of oral antibiotics may enhance BT to the MLNs and other organs after burn injury, which impairs both humoral and cellular immunity in addition to the damage of local barriers. 4,7,8,20,21,23 In the present study, we found that oral antibiotic treatment enhances BT and promotes the spread of translocating bacteria to the liver in burned rats. However, antibiotic treatment is usually required in the treatment of the burn injury victims.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, the administration of oral antibiotics may enhance BT to the MLNs and other organs after burn injury, which impairs both humoral and cellular immunity in addition to the damage of local barriers. 4,7,8,20,21,23 In the present study, we found that oral antibiotic treatment enhances BT and promotes the spread of translocating bacteria to the liver in burned rats. However, antibiotic treatment is usually required in the treatment of the burn injury victims.…”
Section: Discussionsupporting
confidence: 50%
“…15,16,18,19 However, the superimposition of additional stress factors such as manipulation of the intestinal flora, endotoxin challenge, insufficient fluid resuscitation, burn wound infection and sepsis, immunosuppression, or the administration of antibiotics or H 2 -receptor blocking agents increases and prolongs BT to the MLNs and other organs. 4,[15][16][17][18][19][20][21][22][23] On the other hand, BT is reduced when attempts are made to prevent intestinal ischemia by aggressive fluid resuscitation, the inhibition of xanthine oxidase, or the administration of vasodilators, and when attempts are made to prevent intestinal mucosal atrophy by bombesin, insulin growth factor 1, or the enhancement of immune responses by immunoglobulin therapy. 15,16,19,[24][25][26][27] It has been reported that antibiotics promote BT to the MLNs.…”
Section: Discussionmentioning
confidence: 99%
“…According to Alverdy and Aoys 18 , corticosteroid treatment significantly reduces secretory IgA concentration in the intestine. Jones et al 19 found that increasing doses of corticoids prolonged the presence of indigenous and exogenous bacteria in the tissues of mice. They also observed that prednisone can increase the adherence of these bacteria to the intestinal cells facilitating their translocation, besides reducing the host's ability to eliminate the translocated bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…[25,[38][39][40][41] Multiple organ failure is the common denominator of the high death rates due to generalised serious peritonitis and continued peritoneal sepsis. [25,[38][39][40][41] Multiple organ failure is the common denominator of the high death rates due to generalised serious peritonitis and continued peritoneal sepsis.…”
Section: Discussionmentioning
confidence: 99%